Obvious Mistakes in a Strategically Simple College Admissions Environment - Ran I. Shorrer; Sándor Sóvágó (Tinbergen Institute, 2017)
In a centralized marketplace that was designed to be simple, we identify participants whose choices are dominated. Using administrative data from Hungary, we show that college applicants make obvious mistakes: they forgo the free opportunity to receive a tuition waiver worth thousands of dollars. At least 10 percent of the applicants made such mistakes in 2013. Costly mistakes have externalities: they transfer tuition waivers from high- to low-socioeconomic status students, and increase the number of students attending college. To shed light on the mechanisms underlying mistakes, we exploit a reform that substantially increased the selectivity of admission with financial aid in some fields of study. Increased admission selectivity raises the likelihood of making obvious mistakes, especially among high-socioeconomic status and low-achieving applicants. Our results suggest that mistakes are more common when their expected cost is lower. Still, the average cost of a mistake in 2013 was 114-365 dollars.
Keywords: C70; D47; D61; D63; 330; College admissions; dominated strategies; market design; obvious misrepresentation; school choice; strategy-proof